Genetic Diversity and Genome-Wide Association Study for Shoot and Root Traits in Rice Grown Under Water Deficit at Early Vegetative Stage - Gabriel Brandão das Chagas; Rodrigo Pagel Machado; Célanet Fils-Aimé; Antônio de Azevedo Perleberg; Viviane Kopp da Luz; Antonio Costa de Oliveira; Luciano Carlos da Maia; Camila Pegoraro (Stresses)
Water deficit affects rice growth, development, and yield. Knowledge of genetic diversity for water deficit tolerance, as well as the genetic architecture that is responsible for this trait, can accelerate rice cultivars’ improvement. In this study, different tools were applied to assess genetic diversity and identify genome regions associated with shoot and root traits in rice germplasm grown under water deficit at an early vegetative stage. A panel of 177 rice genotypes grown under water deficit was evaluated for root length (RL), root dry weight (RDW), shoot length (SL), and shoot dry weight (SDW). Genetic diversity was investigated using means grouping and principal component analysis. For the genome-wide association study, a general linear model was applied, using RL, RDW, SL, and SDW phenotypic data converted into Best Linear Unbiased Prediction (BLUPs); genotypic data (1185 single nucleotide polymorphism—SNPs-loci); and population structure. Overall, little genetic diversity was observed, but genotypes with a higher water deficit tolerance were identified. Several significant SNPs were mapped, 81, 5, 53, and 41 for RL, RDW, SL, and SDW, respectively. Among the identified genes, there are those encoding kinases, proteins involved in phytohormone and cell wall metabolism, and Cytochrome P450. The obtained results provide insight into genetic diversity and the genetic architecture of water deficit tolerance, which will be useful in improving this trait in rice grown in Brazil.